2018
DOI: 10.1007/s12671-018-1002-4
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Emotional Eating: Mediated by Mindfulness?

Abstract: The association between depressive symptoms and emotional eating has been well established. The aim of the current study was to examine whether the association between depressive symptoms and emotional eating was mediated by mindfulness, a construct that has successfully been implemented in the treatment of eating disorders and depression. Mindfulness, particularly, the component Bacting with awareness^was theorized to decrease impulsive eating. Data from 417 Dutch adult participants were analyzed. Mediation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
1
10
0
1
Order By: Relevance
“…Furthermore, these data are in line with previous research documenting a negative relationship between acting with awareness mindfulness and negative emotional eating in people who are overweight with diabetes (Levin et al, 2014; Ouwens et al, 2015; Tak et al, 2015). More recent research demonstrated that acting with awareness mindfulness fully mediated the relationship between depressive symptomatology and negative emotional eating in the general population, possibly leading to decreased emotional eating (Höppener et al, 2019). The protective effect of acting with awareness mindfulness on the association between emotional eating‐depression and BE should be considered in light of the contrasting effects of non‐reactive mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these data are in line with previous research documenting a negative relationship between acting with awareness mindfulness and negative emotional eating in people who are overweight with diabetes (Levin et al, 2014; Ouwens et al, 2015; Tak et al, 2015). More recent research demonstrated that acting with awareness mindfulness fully mediated the relationship between depressive symptomatology and negative emotional eating in the general population, possibly leading to decreased emotional eating (Höppener et al, 2019). The protective effect of acting with awareness mindfulness on the association between emotional eating‐depression and BE should be considered in light of the contrasting effects of non‐reactive mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with obesity often demonstrate a dysregulated physiological response to intense emotion, known as emotional eating. Specific aspects of emotion dysregulation, such as a lowered tendency to act with emotional awareness ( 58 ), difficulty identifying emotions ( 59 ), and limited access to emotion regulation strategies ( 60 ) have been implicated. A high prevalence of emotion dysregulation in pre-surgery bariatric patients has been shown ( 61 ), and pre-surgery maladaptive eating was in one study initiated by both avoidance (of negative affect) and approach (reward sensitivity) behaviors ( 62 ).…”
Section: Emotion Dysregulationmentioning
confidence: 99%
“…Our study reports data on a large community sample, including males and females, potentially making it more applicable to the general population. Höppener et al (2019) explored the association between mindfulness, depressive symptoms and emotional eating using a multifactorial measure, but their focus was on the mediating effect of this relationship. They found that the only facet to mediate the association between depressive symptoms and emotional eating was acting with awareness.…”
Section: Discussionmentioning
confidence: 99%